IMPLEMENTASI EDUPRENEURSHIP DI MI IMAM SYAFI’I TELAGA KABUPATEN GORONTALO - Moh Syaril Lasena; Imam Mashudi (LPPM Universitas Muhammadiyah Gorontalo, 2025)
The study focuses on the results of interviews with the vice principal, which describe the integration of entrepreneurial skills into the school curriculum. In its implementation, students carried out a project involving the production of fruit ice as part of the learning process. This activity not only enhanced students’ creativity but also improved their collaboration skills and practical competencies in entrepreneurship. Through this project, students learned the entrepreneurial process, starting from planning and production to marketing, providing them with direct exposure to the business world. The interview results indicate that the use of the P5 approach can stimulate students’ interest in entrepreneurship and foster independent and innovative character development. This study is expected to inspire other schools to implement edupreneurship programs and to strengthen the relevance of entrepreneurship education at the elementary school level. Relevant references in this study include theories of project-based learning and entrepreneurship education, as discussed by Hisrich and Peters (2013) and Muliati (2020).